Martín de Rada’s Book Collection - Folch, Dolors (Sinología hispánica. China Studies Review, 2018)
This article will explore the library of the most important of the 16th century Manila based Augustinians, fray Martin de Rada, a well known cosmographer, mathematician and astronomer. After spending more than five years in Mexico, and ten in the Philippines, in 1575 he was assigned to the first Spanish expedition to China and wrote a highly influential Relación about it. From his own letters —14 of them extant—, the letters of his contemporaries about Rada —from Manila, Mexico and Spain—, and the Relación of his fellow traveler to China, Miguel de Loarca, we are able to disentangle his main intellectual interests and the contents of his library: what he wrote —both in Mexico and Asia—, the significance of the scientific works that he took with him to Asia, the importance of the Chinese maps with which he worked while in Manila —before and after his travel to China—, what books he bought in China and what use did he make of them, and the last works in which he was working before his death. This gives Rada a strong intellectual profile that has to be compared with that of his contemporary, the Jesuit Matteo Ricci.